IMPACT OF THE COVID-19 PANDEMIC ON INDONESIAN CAPITAL MARKET (IDX COMPOSITE) - Irzameingindra Putri Radjamin (Journal of Economics, Business, and Government Challenges, 2023)
The COVID-19 pandemic has caused many problems globally. Various sectors have been affected by this pandemic. In this study, we aim to determine the impact of the COVID-19 pandemic on the Indonesian capital market (IDX Composite). The method used in this study is the quantitative method of collecting data on COVID-19 cases in Indonesia in 2020 and 2020 IDX Composite data from the government’s official website. We also use the Granger Causality Test to check the relationship between those two variables. The COVID-19 impact on Indonesian Capital Market can be seen from this study’s result, where the 2020 COVID-19 cases in Indonesia had a quite large impact on Indonesian Capital Market (IDX Composite). When the COVID-19 cases started in Indonesia in March 2020, the IDX Composite experienced a significant decline.